A Novel Approach to the Thermal Management of Internal Combustion Engines. (September 2017) - Castiglione, Teresa; Bova, Sergio; Belli, Mario
Abstract: The paper presents a novel control architecture developed with the aim to satisfy the requirements of the cooling system of an ICE, by means of an electric pump and of an ad-hoc developed control module. The developed controller is based on the Robust Model Predictive Control and is designed with the purpose to satisfy the input and output constraints and to reject the external disturbances, by adopting a lumped parameter model of the engine cooling system, which predicts the coolant temperature, the average wall temperature and the heat transfer regime including nucleate boiling. Given that the proposed methodology is valid for each condition, in the present paper the focus is on the engine operating under fully warmed conditions, with the aim to keep the wall temperature into the prescribed limits, with the lowest possible coolant flow rates. This goal is achieved by properly defining the controller parameters. Different control strategies are proposed and their effectiveness is evaluated in terms of engine wall temperature, coolant temperature, coolant flow rate and heat transfer regime in response to step-wise variations in fuel flow rate. The region of stability of the controller is also discussed. Results show that the control algorithm is robust in terms of disturbance rejections and ensures effective and safe cooling with much lower coolant flow rates if compared to the ones provided by the use of the standard crankshaft driven pump.